Sto tváří, sto příběhů Vybrané osobnosti v dějinách Filozofické fakulty Masarykovy univerzity - Fasora, Lukáš (MUNI ARTS 100, 2020)
Title in English: One Hundred Faces, One Hundred Stories: Selected personalities in the history of the Faculty of Arts of Masaryk University The book commemorating the centenary of the establishment of the Faculty of Arts is also a contribution to the anniversary of the whole Masaryk University. Its aim is to walk through the history of the faculty by means of a biographical method, i.e., using short biographies that introduce representative, prominent or interesting personalities whose fates and work were connected with the faculty. There was certainly no lack of biographical views in the research of the faculty history, still, such a complex set of biograms has not been collected so far. And the publication offers much more: the authors use a large set of biographical data to interpret the history of the faculty from the perspective of alternating academic generations and contemplate the formative generation experience as well as the phenomena that affected the lives of academics and students over the past 100 years. These include, as a matter of fact, both positive and negative phenomena, therefore, the publication is not just an overview of deserving personalities, respected scientists and charismatic teachers, but it also openly discusses the lives of controversial scholars. Thus, the collection of biograms provides a credible testimony to the one-hundred-year work of the faculty, continually blending studies, science and politics.